Burnout and psychological distress among childminders in residential childrens' homes / Siti Halimatul Saadiah Hassan - Siti Halimatul Saadiah , Hassan (2016)
Childminders in residential homes are often faced great challenges, when dealing with childrens’ behavioural and emotional difficulties. This contributes to psychological distress and burnout among these caregivers. Burnout among childminders give impact on the childcare and it affects the children’s life as well as the caregiver in the long term. Burnout has three categorizations consist of exhaustion (EX), cynicism (CY) and personal efficacy (PE). Aim The primary objective was to determine the proportion of burnout and psychological distress of childminders and identify their relationship with sociodemographic variables. The second objective was to assess the correlation between burnout and psychological distress. Method This was a cross sectional study done among childminders in Kuala Lumpur and Selangor. A total of 150 childminders were selected using universal sampling from 30 children homes between July to October 2015. Assessments were carried out using the Maslach Burnout Inventory- General Survey (MBI-GS) and the Depression Anxiety Stress (DASS-21) scale as the self-reported questionnaires. The relevant personal and socio-demographic data were also collected. The ethical approval for the study was obtained from the Ethics Committee of University Malaya Medical Centre. The data were analysed using SPSS (version 22). Result: The level of burnout (high) was based on each domain and noted to be 31.3% (n=47) for CY, 28.7% (n=43) for EX and 36% (n=54) for reduced sense of PE. The proportion of the v severe burnout (EX+CY) among the childminders was found at 24.7% (n=37). By attending early childhood training (adjusted OR 0.42, 95% CI 0.18, 0.99), perceived inadequate staff (adjusted OR 0.40, 95% CI 0.17, 0.96) and not working in shift system (adjusted OR 3.41, 95% CI 1.28, 9.07) were significantly associated with EX. The childminders prone to have decrease sense of PE (adjusted OR 4.18, 95% CI 1.15, 15.19). Childminders who had symptoms of stress (adjusted OR 0.24, 95% CI 0.09, 0.68) or not attended early childhood training (adjusted OR 0.30, 95% CI 0.11, 0.79) were at risk of severe burnout. The childminders with 4 children or less at home (adjusted OR 8.5, 95% CI 1.45, 50.39), childminders who were EX (adjusted OR 0.4, 95% CI 0.17, 0.90) or who experienced severe burnout (adjusted OR 0.28, 95% CI 0.09,0.85), were prone to exhibit depressive symptoms. Those childminders who had job stability (adjusted OR 0.30, 95% CI 0.13, 0.68), or were exhausted (adjusted OR 0.15, 95% CI 0.06, 0.37), were prone to anxiety symptoms. Female childminders (adjusted OR 0.34, 95% CI 0.13, 0.90), childminders who demonstrated EX (adjusted OR 0.2, 95% CI 0.08, 0.51) or childminders with severe burnout (adjusted OR 0.24, 95% CI 0.08,0.72), were more likely to develop symptoms of stress. There was a moderate correlation between severe burnout and psychological distress (r= 0.51) to (r=0.60). Conclusion: These high levels of burnout and symptoms of psychological distress among our childminders, are of great concern to healthcare providers. Screening and detection of burnout and psychological distress among these carers is crucial, as they serve as caregivers to a very vulnerable group: young children and adolescents in residential homes. It is recommended that screening of these symptoms be conducted in all residential homes to ensure quality of care. Referral to the mental health services may be required for further evaluation and treatment when indicated. As this study is the first research done in Malaysia in this area, it can be used as a stepping stone to begin effective intervention programmes that are relevant in the local vi setting for the betterment of childminders’ mental health and child-care services in the region of South East Asia.